Analisis Daya Dukung Lahan Tanaman Perkebunan di Kabupaten Banggai - Katili, Hidayat Arismunandar; Sataral, Mihwan (Department of Agribusiness, Halu Oleo University, 2020)
Land use plan based on agricultural land support sub-plantation sector can address the needs and availability of a more productive plantation commodity, and economically profitable. This research aims to analyze the availability and needs of the land and determine the supporting capacity of plant land in Banggai Regency. This research was conducted from June to August 2020, used qualitative methods that are analyzed in quantitative decorative where the research covers 12 plantation plant commodities in Banggai Regency. The data used in this study are primary and secondary data from BPS-Statistics of Banggai Regency and Department of Food Crops, Horticulture and Plantation of Banggai Regency in 2020. Data collection is carried out with observation in the field and secondary data tracking from Statistics Center, Banggai District, and The Office of Food Crops, Horticulture, Plantation Banggai Regency. Furthermore, the calculation based on Permen LH No. 17 of 2009, where the Status of Land Support Capacity obtained from the comparison between land availability and land needs until the determination of land support capacity is declared surplus/deficit. The results showed that the availability of land from the 12 highest plantation commodities in Cocoa (143,200 ha), and the low availability of land in Kapuk commodity (24.38 ha). The analysis of the land needs of 12 plantation commodities showed that the commodities that have the highest land are tobacco (905,788.46 ha) and the lowest in coconut commodities (13,979.67 ha). The comparison between land availability and land needs in 12 plantation commodities in Banggai Regency, obtained by Oil, Palm Oil, Clove, and Cocoa crops is Surplus. This commodity is overloaded, this indicates that the availability of land in Banggai district is able to meet the needs of land to live decently per population.